Constitutional aspects of the price control of petroleum products - Zagorc, Saša (Anali PAZU HD, 2022)
Due to noticeable price increases and corresponding volatility of oil and gas in recent years, public and political interest as concerns a stable provision of propellants augmented substantially. Such price fluctuations affect not only national economies but also actions of consumers. Relevant stakeholders on the market freely determine retail price of petroleum products in many countries. Nevertheless, it is quite common that the public and, consequently, politicians reject an option for dynamic price changes. This is often in stark contrast with a general policy and 92 ANALI PAZU HD, let. 2, 2/2016, 91‒111 Saša Zagorc guidelines of national competition regulators that an authoritative intervention in process of price determination is not necessary. Slovenia belonged for a long time to the group of countries with price control of petroleum products for end users despite the principled stance on free enterprise and free economic initiative. In this regard, author would like to establish an appropriate methodological approach, in line with the case law of the ECrtHR and the Constitutional Court, for a review of constitutionality and legality of executive measures. Author also assessed if the Government fully respected the principles of legality, foreseeability and strict proportionality of executive measures for price control of petroleum products.